Formación de un híbrido simple de maíz tipo dulce, en base a las líneas del ICA H.S. 209. - Rubio Barragán, A.M.; Muñoz G, S.; Arboleda Rivera, F.; Sarria V, D. (Instituto Colombiano Agropecuario, 2018)
Maíz-Zea mays